Airliners of the 2000s - Manning, Gerry (Stamford : KEY Books, 2022)
With over 300 colour photographs with extended and informative captions, this book details the many facets of commercial air transport around the world, from the smallest to the largest airlines.
Keywords: Airplanes -- History; Airplanes; Airplanes -- History -- Pictorial works